DETERMINANTS OF PARENT’S DECISIONS IN IMMUNIZING MEASLES RUBELLA (MR) VACCINE - Devi Maya Arista; Dwiyanti Puspitasari; Sri Utami (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: The government’s effort to reduce measles and rubella transmission are by increasing MR immunization coverage. The immunization coverage was influenced by parent’s decisions. There were factors that related with parent’s decisions such as knowledge, perceived susceptibility, seriousness, benefit, barrier, self-efficacy, and cues to action. This study aimed to analyze factors  related with parent’s decisions in giving MR immunization. Methods: This was a cross sectional study using questionnaire among parents of children aged 10-30 months at working area of Kenjeran public health center, Surabaya. Data of knowledge, perceived susceptibility, seriousness, benefit, barrier, self-efficacy, and cues to action regarding MR immunization then analyzed using chi-square and logistic regression. Result: From 206 parents, 56.3% were giving MR immunization to their children. Parent’s knowledge (p=0.023; OR=18.08), perceived barrier (p=0.002; OR=46.79), and self-efficacy (p=0.033; OR=7.66) were related with parent’s decisions. Conclusion: Parent’s decisions in giving MR immunization was related with knowledge, perceived barrier, and self-efficacy.